Cybersecurity Risks in Digital Finance: Regulatory and Ethical Challenges in Protecting Consumers - Anggun Wida Prawira; Tiago Costa; Clara Mendes (Yayasan Adra Karima Hubbi, 2025)
The rapid growth of digital finance has transformed financial services by providing convenience, accessibility, and efficiency. However, this digital expansion also introduces significant cybersecurity risks, including data breaches, fraud, and unauthorized access, which threaten consumer protection and trust. Regulatory frameworks and ethical guidelines are critical to mitigating these risks, yet the evolving nature of technology presents ongoing challenges for policymakers and financial institutions. This study investigates cybersecurity risks in digital finance and examines the regulatory and ethical measures implemented to protect consumers. A qualitative research design was employed, combining systematic literature review with analysis of case studies involving cybersecurity incidents and regulatory responses in the financial sector. Data were analyzed thematically to identify patterns in risk exposure, regulatory effectiveness, and ethical considerations. Findings indicate that despite regulatory initiatives, gaps persist in data protection, enforcement, and alignment with emerging technologies, leaving consumers vulnerable to financial and informational harm. Ethical challenges include balancing innovation with responsibility, transparency in data use, and accountability for breaches. The study concludes that comprehensive, adaptive regulatory frameworks coupled with strong ethical standards are essential to safeguard consumers in digital finance. Collaboration among regulators, financial institutions, and technology providers is crucial to anticipate risks, ensure compliance, and foster trust in the digital financial ecosystem.